Migrasi Orang Biak dan Identitas Orang Asli Papua di Sausapor, Papua Barat - Irin Oktafiani; Herry Jogaswara (Antropologi Indonesia, 2019)
This paper discusses the migration process and the recognition of identity of Biak people in Sausapor along with the impact of it. Dichotomy of local and outsider is still a clear barrier separating Biak and Abun people in Miossu islands and Sausapor, the capital district of Tambrauw, West Papua. Biak people are considered as outsider with regards to the land ownership issue in Sausapor. On the other side, they are also considered as insider in Kampung Werur which is located in the same region with Sausapor. There are two different identity layers related to the problem of land ownership and ethnicity sentiment. The problem of locals and outsiders in this paper is coming from the small scale point of view and is examined through the perspective of the indigenous Papuans. Data was collected through in-depth interview and observation during a short visit in Kampung Werur and Sausapor as a part of Ekspedisi Nusa Manggala 2018. This paper concludes that the identity of Biak people should be seen through the contextualization and with whom they interact. Their identity as Biak People comes as manifestation of confession and recognition within themselves and by the others.